Bougainvillea glabra (choisy): A comprehensive review on botany, traditional uses, phytochemistry, pharmacology and toxicity. (10th February 2021) - Saleem, Hammad; Usman, Atif; Mahomoodally, Mohamad Fawzi; Ahemad, Nafees
Abstract: Ethnopharmacological relevance: Bougainvillea glabra (Choisy). (Family: Nyctinaginacea) is a valuable ornamental plant with culinary uses and also utilized in traditional medicine for treating common ailments. It is traditionally employed against several diseases such as diarrhoea, hypotension, intestinal disorders, stomachache, nausea, inflammation-related ailments, and in pain management. Though widely validated via in vitro and in vivo models, to date no endeavour has been made to compile in a single review the traditional, phytochemistry and pharmacological properties of B. glabra . Aims: To provide an up-to-date, authoritative review with respect to the traditional uses, chemical composition, in vitro and in vivo pharmacological properties, and toxicological estimations accomplished either utilizing the crude extracts or, wherever applicable, the bioactive compounds isolated from B. glabra . Besides, a critical evaluation of the published literature has been undertaken with regards to the current biochemical and toxicological data. Materials and methods: Key databases per se, Ovid, Pubmed, Science Direct, Scopus, and Google scholar amongst others were probed for a systematic search using keywords to retrieve relevant publications on this plant. A total of 52 articles were included for the review depending on Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Results: The studies conducted on either crude extracts, solvent fractions or isolated pure compounds from B. glabra had reported a varied range of biological effects comprising antibacterial, antifungal, antidiabetic, cytotoxic, analgesic, antipyretic, anti-inflammatory, and antioxidant activities. Phytochemical analysis of different parts of B. glabra unveiled 105 phytochemicals, belonging to phenolic, flavonoid, betacyanin, terpenoid, glycoside and essential oils classes of secondary metabolites. Conclusion: Most of the pharmacological activities of crude extracts from this plant have been reported. A very few studies have reported the isolation of compounds responsible for observed biological potential of this plant. Moreover, the toxicity studies of this plant still need to be explored comprehensively to ensure its safety parameters. Additional investigations are recommended to transmute the ethnopharmacological claims of this plant species in folklore medicines into scientific rationale-based information. Graphical abstract: Image 1